KELUARGA BERENCANA (KB) MENURUT HUKUM ISLAM DAN IMPLIKASINYA DALAM MEMBINA KELUARGA SAKINAH (STUDI KASUS DI DESA BLANG CRUM KECAMATAN MUARA DUA KOTA LHOKSEUMAWE) - Janiati, Cut (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
The Family Planning Program (KB) according to Islamic law is permissible (Mubah) if it is carried out as a form of family birth control/sparing births or a temporary pregnancy prevention effort in connection with special situations and conditions for the benefit of the family concerned or for the benefit of the people. Furthermore, the Family Planning (KB) program is illegal (Haram) if the goal is to limit a certain number of families/children, for example two or three children for each family in all situations and conditions without exception. This study examines the causative factors that cause the people of BlangCrum Village, Muara Dua District, Lhokseumawe City to participate in the Family Planning (KB) program, using qualitative research using library research and field research methods. Based on the results of the study, it can be concluded that the factors causing the people of BlangCrum Village, Muara Dua District, Lhokseumawe City to participate in the Family Planning (KB) program are as follows: Practicality because they are busy with work, maternal and child health, family economic ability, religious interests, desire to raise children well and psychological factors.The Family Planning Program (KB) which is participated in by residents of BlangCrum Village, Muara Dua District, Lhokseumawe City, has implications for fostering a sakinah family in the village, namely; improving maternal health and harmonious marital relations, influencing children's intelligence and health, fulfilling care and affection for children and achieving well-being of life.